Impacts of foot-and-mouth disease on livelihoods in the Borena Plateau of Ethiopia. - Jibat, Tariku.; Admassu, Berhanu.; Rufael, Tesfaye.; Baumann, Maximilian PO.; Pötzsch, Carsten J. (2016)
Abstract: This study was conducted to estimate impacts of foot-and-mouth disease (FMD) on producers' livelihoods in Borena zone, southern Ethiopia, using participatory appraisal methods and secondary data sources. Livestock-related livelihood options accounted for 31% of the total means of food and income sources followed by crop farming. This study clearly showed that FMD had the greatest impact on the cattle-derived benefits. FMD outbreak frequencies were found to be significantly correlated to the length of extended dry season (r = 0.377). In addition, FMD is ranked as the number one cattle disease after 1985 with significant rank change (t = 12.04) as compared to 1984 and before. Considering the impacts of FMD on peoples' livelihoods, FMD effective control strategies would reduce stress on people's lives, improve food security and keep social harmony.; Keywords: Foot-and-mouth disease, Participatory epidemiology, Socio-economics, Pastoralists, Ethiopia.; Springer Open.